Forklift chain wheel with chain twisting prevention function - ZENG LIJIAO (2021)
The invention discloses a forklift chain wheel with a chain twisting prevention function. The forklift chain wheel comprises forklift fixing round steel, the surface of the forklift fixing round steel is fixedly connected with the inner surface of a bearing, the outer surface of the bearing is fixedly connected with the inner surfaces of chain teeth, and the surfaces of the chain teeth are movably connected with the surface of a chain. The surface of the chain is movably connected with the surfaces of chain baffles, the surface of the chain is movably connected with the surface of a chain positioning plate, and the surface of the chain positioning plate is fixedly connected with the bottom end of a connecting rod. According to the forklift chain wheel with the chain twisting prevention function, a chain cover, the chain, a first spring, the connecting rod, the chain positioning plate, the chain teeth and the chain are arranged, the first spring on the surface of the chain cover is fixedly connected with the c